The Effect of Financial Constraints and Institutional Ownership on Tax Agressiveness - Nurul Aisyah Rachmawati; Ana Fitriana (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
Tax aggressiveness is an action taken by a company in reducing taxable income through tax planning, either legally done by tax avoidance or illegally by tax evasion. This study examines the effect of financial constraints and institutional ownership on tax aggressiveness.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sampling method used in this research is purposive sampling, with this method companies that meet as many as 56 companies. The analytical tool used is classic assumption test, multiple linear regression test, model test and hypothesis test. The results of this study indicate that (1) financial constraints have a positive effect on tax aggressiveness, (2) institutional ownership has a positive effect on tax aggressiveness, (3) institutional ownership weakens the relationship between financial constraints and tax aggressiveness.